Design of modular dual enzyme‐responsive peptides. Issue 5 (11th August 2017) - Boehnke, Natalie; Maynard, Heather D.
Abstract: Dual enzyme‐responsive peptides were synthesized by masking the ɛ‐amine of lysine with various enzyme substrates. Enzymatic cleavage of these sequences unmasked the ɛ‐amine, allowing for further digestion by a second enzyme, which was monitored colorimetrically. This modular peptide design should provide substrates for a large combination of clinically relevant enzymes. Abstract :